Re-examine the influence of organizational identification on unethical pro-supervisor behavior - Sun, Tuwei; Shi, Wei; Wang, Jing (Frontiers in Psychology, 2022)
Employees’ unethical pro-supervisor behavior (UPSB) is common in organizations. Existing research primarily argued that organizational identification increases this behavior, emphasizing that UPSB benefits organizations indirectly. However, it ignores that UPSB can sometimes serve the interests of the supervisor at the expense of the interests of the organization. Drawing on social identity theory and social cognitive theory, this study aims to emphasize this point by proposing that organizational identification can inhibit employees’ UPSB via the mediation of felt obligation. We also propose that perceived organizational cronyism would weaken the negative effect. Data were collected through a self-reported online questionnaire based on a three-wave research design and analyzed through hierarchical regression analyses. With a sample of 578 Chinese employees, we found support for our propositions. Implications and limitations are discussed.